Increased non-major histocompatibility complex-restricted lytic activity in melanoma patients vaccinated with cytokine gene-transfected autologous tumor cells - Möller, Peter; Sun, Yuansheng; Schadendorf, Dirk (Cancer gene therapy, 2000)
Genetically modified antitumoral vaccines focus on eliciting or increasing the T-cell-mediated antitumoral response. Little is known about non-major histocompatibility complex-restricted responses. In two phase I studies, we have immunized advanced melanoma patients with either interleukin-7 (IL-7) gene-transfected or IL-12 gene-transfected, autologous, irradiated melanoma cells. To monitor the immune response, peripheral blood mononuclear cells were collected before the first vaccination and 2 weeks after the third vaccination. Spontaneous lytic activity and lymphokine-activated killer (LAK) activity after a 5-day culture in the presence of 1000 U/mL IL-2 against autologous and against allogeneic melanoma cells were measured. In parallel, a precursor cytotoxic T-cell frequency analysis was performed using a 25-day limiting dilution analysis assay. A total of 10 of 14 immunologically evaluable patients demonstrated a marked increase in LAK activity, and 7 of 14 showed increased spontaneous lytic activities against autologous melanoma cells after three vaccinations. Remarkably, two patients with a good clinical performance status (Karnofsky index of >70; Multitest Merieux of >13.4 mm/3) and the highest cytotoxic T-lymphocyte (CTL) response after vaccination showed the only clear decrease in LAK and spontaneous lytic activity. Otherwise, three patients with no detectable CTL response after vaccination demonstrated an increase in LAK activity and the strongest increase in the autologous spontaneous lytic activity. This group of patients was associated with a poor clinical performance status (Karnofsky index of <70; Multitest Merieux of <4 mm/1) and with no clinical response. In conclusion, in accordance with other studies, a good clinical and immunological performance status appears to be the prerequisite for a successful CTL response. However, even strong non-major histocompatibility complex-restricted responses could be generated in patients with reduced clinical performance in vaccination therapies with gene-transfected autologous tumor cells.
Gesehen am 26.02.2019